THEORETICAL PRINCIPLES OF INCREASING ECONOMIC EFFICIENCY ON THE BASIS OF THE LEAN PRODUCTION SYSTEM IN INDUSTRIAL ENTERPRISES (Marketing Journal, 2026)
This article examines the theoretical foundations of Lean Manufacturing and its impact on the economic efficiency of industrial enterprises based on a systematic literature review . The study draws upon the principles of the Toyota Production System and the five core Lean principles developed by Womack and Jones . It analyzes the mechanisms through which tools such as 5S, Kaizen , JIT, VSM, TPM, and Kanban № 1 -SON YANVA R, 202 6-YIL 573 influence production performance . The findings indicate that Lean implementation enhances labor productivity , reduces inventory levels , and minimizes operational waste , thereby strengthening enterprise competitiveness . The paper also provides practical recommendations for the phased implementation of Lean systems in developing economies .
Keywords: Lean Manufacturing; economic efficiency; Toyota Production System; 5S; Kaizen; Just-in-Time; waste elimination; industrial enterprises; continuous improvement